Persuasive Communication Strategies Of Leaders In Reducing Serious Disciplinary Violations Among Soldiers (Multi-Site Study At The Signal Battalion Of Pushubad And Battalion 21 Group 2 Kopassus) - Eka Indri Widarti; Astriana Baiti Sinaga (Journal of Social Research, 2025)
In essence, the leadership culture in military organizations is instructive and authoritarian with one command center. However, it is possible that a persuasive communication strategy was used by the leaders of the Yonhub Pushubad and Yon21 Group 2 of Kopassus to reduce the number of cases of soldiers’ offenses. This study aims to determine, compare and synthesize leadership persuasive communication strategies in suppressing the level of soldier discipline offenses in Yonhub Pushubad and Yon 21 Group 2 Kopassus. The method used in this research is a qualitative method and a descriptive approach with a multi-site study at the Yonhub Pushubad and the Yon 21 Group 2 Kopassus. Primary and secondary data collection techniques through in-depth interviews, participant observation and documentation. Based on the analysis and discussion of all the findings and data collected, it was concluded that the leaders of Yonhub Pushubad applied psychodynamic, psychocultural and the meaning construction persuasive communication strategies to reduce the number of infringements among its soldiers. On the other hand, the leaders of Yon 21 Group 2 Kopassus also applied the same three persuasive communication strategies to minimize the number of transgressions by its soldiers. Although both sites use the same persuasive communication strategies, different ways and methods are implemented by each leadership group in their unit. From the description of the results of the study, it can be concluded that the leaders of Yon 21 Group 2 Kopassus are more persuasive than the leaders of the Yonhub Pushubad, as can be seen from the variety and effectiveness of the communication strategies applied in controlling the discipline of its members. This is also evidenced by the percentage of offenses by soldiers of Yon 21 Group 2 Kopassus which is smaller than Yonhub Pushubad from 2018 to 2021.